2020
DOI: 10.1186/s12955-020-01570-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health-related quality of life decline in interstitial lung disease

Abstract: Background Health-related quality of life (HRQL) in interstitial lung disease (ILD) patients is impaired. We aimed to identify baseline predictors for HRQL decline within a 12-month observation period. Methods We analyzed 194 ILD patients from two German ILD-centers in the observational HILDA study. We employed the disease-specific King’s Brief Interstitial Lung Disease questionnaire (K-BILD) with the subdomains ‘psychological impact’, ‘chest symptoms’ and ‘breathlessness and activities’, and the generic EQ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In line with our findings, illness perception positively associated with fear of progression (Shim et al, 2018). As the disease progresses, the exacerbation of patients' symptoms, the increase in economic cost and the accumulation of side effects will cause psychological, physiological and social impacts on patients (Maqhuzu et al, 2020;Yuan et al, 2019). At this time, it is necessary to accept the diagnosis and treatment of ILD emotionally and psychologically.…”
Section: Discussionsupporting
confidence: 85%
“…In line with our findings, illness perception positively associated with fear of progression (Shim et al, 2018). As the disease progresses, the exacerbation of patients' symptoms, the increase in economic cost and the accumulation of side effects will cause psychological, physiological and social impacts on patients (Maqhuzu et al, 2020;Yuan et al, 2019). At this time, it is necessary to accept the diagnosis and treatment of ILD emotionally and psychologically.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, other studies that have investigated HRQOL with disease specific tools in Chronic Obstructive Pulmonary Disease and ILD also did not identify a significant association between HRQOL and pulmonary function parameters. 19,20 Taken as a whole, other objective markers of disease severity such as pulmonary hemodynamics, laboratory values and pulmonary function measurements did not directly translate to impairments in HRQOL in PH-CLD. While the lack of association between HRQOL and pulmonary hemodynamics and lung function may be related to the length of time between diagnostic information and PRO assessment, such findings suggest that variables traditionally prioritized for disease assessment in clinical practice are not strongly associated with PROs.…”
Section: Discussionmentioning
confidence: 96%
“…Our study showed that the DLCO %pred, but not FVC %pred, is a significant predictor of poor K-BILD total, ‘psychological’ and ‘breathlessness and activities’ domains in ILD patients. Indeed, a lower baseline DLCO %pred is associated not only with poorer HRQL ( 25 , 34 ) but also with future HRQL deterioration ( 16 , 41 ). Even though the degree of reduction in DLCO usually mirrors the corresponding drop in FVC, a severe reduction in DLCO may represent the presence of pulmonary hypertension on top of lung parenchymal destruction from ILD, and pulmonary hypertension has been shown to decrease the quality of life in IPF patients ( 42 ).…”
Section: Discussionmentioning
confidence: 99%